The Effect of Slow Deep Breathing Technique on Mother's Anxiety During IUD Contraceptive - Khairul Aslamiah; Sri Martini; Nesi Novita (Journal of Maternal and Child Health Sciences (JMCHS), 2023)
The IUD is one of the choices of methods or methods of contraception that are used in the long term to regulate distance and delay pregnancy. One of the obstacles in installing an IUD is the level of anxiety felt by the mother. As an effort to reduce anxiety by using slow deep breathing techniques. To determine the effect of the slow deep breathing technique on maternal anxiety during the installation of IUD contraception at PUSRI Palembang Hospital in 2023. This type of research was a quasi-experimental study with a one group pre-test and post-test approach. The sample in this study were mothers who would install IUD contraception as many as 31 respondents. Data analysis using Paired T Test. The average anxiety score before the intervention was 18.84, while the average anxiety score after the intervention was 9.74. There was a decrease in the anxiety level score before and after the intervention was 9.1 with the results of the P value statistical test 0.000. So that there is an effect of the slow deep breathing technique on the anxiety of IUD family planning acceptors. There is a significant difference between pre and post anxiety scores, which means that the slow deep breathing technique can reduce maternal anxiety when installing IUD contraception.